TINJAUAN KOREOGRAFI TARI SAMBUT SEBIDUK SEHALUAN DI MARTAPURA KABUPATEN OKU TIMUR SUMATERA SELATAN - Rahmi Ul Fadhilah; Indrayuda Indrayuda; Herlinda Mansyur (SENDRATASIK UNP, 2018)
Abstract This article aimed to describe the choreography of Sambut Sebiduk Sehaluan dance in Martapura, East OKU Regency, South Sumatera.This research was conducted by using descriptive analysis of qualitative design. There were primary and secondary data. The object of the research was Sambut Sebiduk Sehaluan dance in Martapura. The main instrument was the researcher herself and the additional instruments were stationary and camera. The data were collected through library research, observation, interview and documentation. The data were analyzed based on the following theory: data collection, data reduction, interpretation, and making inference. The result showed that the analysis was seen from the form and the content of the dance. The form of the dance included the dancers (5female dancers), movement (15 original motives), floor pattern (straight line and V straight line), top design (dominated by the low-top design), group composition (simultaneously and alternately), music (kulintang tanjung kemala), costume and make-up (baju kurung and red songket of Tanjung Batu; beautiful make-up). The content included: idea of Sambut Sebiduk Sehaluan was created in order to greet special guests visiting Martapura and atmosphere of this dance were happiness, peace and elegance. Keywords: review of Dance choreography, Greet Sebiduk Favors